DEKONSTRUKSI EKSEKUSI HAK TANGGUNGAN DALAM MENINGKATKAN PERLINDUNGAN DAN KEPASTIAN HUKUM - Rivai Kusumanegara (Faculty of Law, Trisakti University, 2021)
There are three execution attempts according to the provisions of Law No. 4 of 1996 concerning Mortgage on Land and Land Related Objects, i.e. parate executie, title eskekutorial and sale of Mortgage underhand. However, the execution that should be a protector for creditors is considered to have issues that may harm creditors. This is not without reason, because in the process many events can hinder this execution, such as the object of mortgage is still controlled by the debtor and physical resistance occurs at the time of eviction so that it reduces buyers’ interest and adds cost to the auction winner on the eviction, even though the auction winner has bought the same with highest price through auction. Based on said matter, the researchers considered this research very useful for finding solutions based on previous studies. Keywords : Mortgage, Execution, Auction, Eviction.